The blackhouse : a novel [large type] - Johnstone, Carole (Carole L.) (Thorndike Press large print core series., 2023)
"Robert Reid moved his family to Scotland's Outer Hebrides in the 1990s, driven by hope, craving safety and community, and hiding a terrible secret. But despite his best efforts to fit in, Robert is always seen as an outsider. And as the legendary and violent Hebridean storms rage around him, he begins to unravel, believing his fate on the remote island of Kilmeray cannot be escaped. For her entire life, Maggie MacKay has sensed something was wrong with her. When Maggie was five years old, she announced that a man on Kilmeray--a place she'd never visited--had been murdered. Her unfounded claim drew media attention and turned the locals against each other, creating rifts that never mended. Nearly twenty years later, Maggie is determined to find out what really happened, and what the islanders are hiding. But when she begins to receive ominous threats, Maggie is forced to consider how much she is willing to risk to discover the horrifying truth" --